Pelatihan Membuat Diagram Alir Data Menggunakan Microsoft Word di SMAN 1 Praya Tengah - Marzuki Darusman; Maulana Ashari; Sofiansyah Fadli (Universitas Maritim AMNI Semarang, 2023)
Microsoft office is software that should be mastered by students at the junior and senior high school levels. However, students in this area still do not understand and master the use of the software. Departing from the problems experienced by the younger generation, Microsoft Office introduction and training activities were held to create flowcharts to improve basic computer skills for teenagers. The training was carried out directly at the Computer Laboratory of SMAN 1 Praya Tengah. There were 100 participants in the training and they came from class X. From this material, students were able to get to know the methods for making flowcharts using Microsoft Word. Based on the results after the training during the PKM activities took place, it showed that it was almost 100%. This is evidenced by the very good response and giving a positive assessment of the training provided which reached 66.7%, the implementation of the training reached 75%, and the material stimulus in the training reached 66.7%.